EFEKTIVITAS MIKROALGA Chlorella vulgaris DAN Spirulina plantensis DALAM BIOSORPSI LOGAM NIKEL DI PERAIRAN (KASUS PERAIRAN POMALAA KABUPATEN KOLAKA) - Ahmad Zakir; I Wayan Budiarsa Suyasa; Ida Ayu Astarini (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2022)
Mining and nickel processing activities in Pomalaa, Kolaka Regency have an impact on the condition of coastal waters. Several researchers who have conducted research in the area stated that the Pomalaa coast has been polluted by the presence of nickel metal so that there is an initiative to reduce the impact of Ni in the waters by bioremediation of the microalgae Chlorella vulgaris and Spirulina platensis. This study aims to analyze the growth of microalgae types C. vulgaris and S. platensis cultured on media containing nickel with different concentrations and also to determine the ability of microalgae to reduce nickel heavy metals at different concentrations. This research was carried out at the Fisheries Laboratory of Haluoleo University , while the AAS (Atomic Absorption Spectrophotometric) analysis was carried out at the Kendari Environmental Laboratory UPTD Laboratory on January – May 2021. The results of the analysis showed that there was a significant difference in the growth density of microalgae cells (C. vulgaris and S. platensis) which were given the treatment/concentration. Ni different. The absorption capacity of C. vulgaris ranged from 0.73 to 4.97 mg/l, while s. platensis ranged from 0.082 – 2.11 mg/l. C. vulgaris is superior in reducing nickel because C. vulgaris can live in polluted water conditions. Keywords: Bioremediation; Nickel; C. vulgaris; S. platensis.